Development of CoAP protocol for communication in mobile robotic systems using IoT technique - Chandra Sarkar; Amitava Das; Ravi Kant Jain (Scientific Reports)
Abstract This paper proposes a novel design methodology of Constrained Application Protocol (CoAP) protocol for an IoT-enabled mobile robot system to operate remotely and access wirelessly. These devices can be used in different applications such as monitoring, inspection, robotics, healthcare, etc. For communicating with such devices, the different frameworks of IoT can be deployed to attain secured transmission using different protocols such as HTTP, MQTT, CoAP, etc. In this paper, the novel IoT-enabled communication using the CoAP protocol in mobile robotic systems is attempted. A mathematical analysis of the CoAP model is carried out where this protocol provides a faster response within less time and less power consumption as compared to other protocols. The main advantage of the CoAP protocol is to facilitate Machine-to-Machine (M2M) communication which contains features like small packet overhead and less power consumption. An experimental prototype has been developed and several trials have been conducted to evaluate the CoAP protocol’s performance for rapid communication within the mobile robotic system. Signal strength analysis is also carried out. This reveals that the reliability of sending signals is up to 99%. Thus, the application of the CoAP protocol shows enough potential to develop IoT-enabled mobile robotic systems and allied applications.